Analisis Kepuasan Wisatawan dengan Pendekatan Bauran Pemasaran di Desa Wisata Rumah Dhome - Nugroho, Dhimas Setyo (Sekolah Tinggi Pariwisata AMPTA, 2019)
To be able to support the success of the tourist village destination, marketing activities can be done by using all marketing tools in the form of products, prices, locations, and promotions, which are often called the marketing mix to get tourist satisfaction so that it can result in long term prosperity. In this study, a closed questionnaire was given to tourists incidentally. Documentation and literature studies are carried out to support existing data. The data analysis technique uses multiple linear regression. The results showed that all marketing mix variables significantly influence tourist satisfaction both simultaneously and partially. In this study, the most influential variable in satisfaction is promotion.